Developing the Institution of the Assembly of the People of Kazakhstan in the Context of Forming a Fair Kazakhstan - Amangosov, Ye.R.; Pusyrmanov, N.S.; Zhakiyanov, T.Zh.; Orazbekova, G.B. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This paper examines the evolutionary development of the Assembly of the People of Kazakhstan (APK), an important structural component of the country's political system and an institution that promotes inter-ethnic harmony. The analysis is based on program documents that reveal the different stages of development and provide insights into its transformation. The article is based on institutional design and theoretical develop- ments by B. Jessop and E. Yesengarayev. It provides an understanding of the role of the APK in harmonising inter-ethnic relations. The paper emphasises the social and legal interdependence required to adapt to dynam- ic socio-demographic conditions. The article considers the development of the APK in the context of the for- mation and assembly of the nation of Kazakhstan following the collapse of the USSR. It offers a new per- spective on the evolutionary path of the APK and its implications for strengthening social cohesion in Ka- zakhstan. The authors emphasise the institution's ability to navigate complex inter-ethnic dynamics. This study contributes to the existing literature by offering novel insights into the evolutionary journey of the APK and its implications for fostering social cohesion in Kazakhstan.
Әділетті Қазақстан қалыптастыру контексіндегі Қазақстан халқы Ассамблеясы институтының дамуы
Развитие института Ассамблеи народа Казахстана в контексте формирования Справедливого Казахстана
Keywords: Political institution; interethnic relations; institutional design; Assembly of the People of Kazakhstan; Fair Kazakhstan; Development; Evolution; Nation-building; ethnic groups; national unity